Evaluation Of Oats (Avena Sativa L.) Genotypes For Β-Glucan, Grain Yield And Physiological Traits (Applied Biological Research, 2014)
The present investigation was undertaken to identify suitable cultivars  for commercial grain production for human consumption on the basis of  nature of inter-relationship between β-glucan, grain quality and yield.  The experimental material comprised of ten oats (Avena sativa L.)  genotypes which were evaluated under temperate conditions of Kashmir  for chlorophyll content, leaf area index, grain protein content, β-glucan  content and grain yield. The highest chlorophyll content and leaf area  index was recorded in genotype SKO-211 and highest grain protein in  genotype SKO-209. The highest β-glucan and grain yield was achieved  in genotype SKO-208. Correlation studies on the degree of  interrelationship between various parameters revealed that grain yield  exhibited a significant positive genotypic correlation with chlorophyll  content, leaf area index and β-glucan. From the study it appears oats genotypes viz., SKO-208, SKO-209 and SKO-207 may be suitable for  commercial grain production for human consumption on the basis desirable grain quality characteristics and grain yield but these  genotypes need further testing under different environments.
Keywords: Avena sativa; β-glucan; chlorophyll; genotype; oats; protein; yield